THE EFFECT OF TEMPERATURE AND NITRATE COMPOUND ON GROWTH, BIOMASS AND FREE FATTY ACID CONTENT ON MICROALGAE CULTURE OF Spirulina sp. and Skeletonema sp. - Rukminasari, Nita; Lukman, Muhammad; Tambaru, Rahmadi; Inaku, Dwi Fajriyati; Suharto, Suharto (Universitas Negeri Semarang, 2018)
Temperature and availability nutrients played an important role on growth and lipid production of microalgae. In this study, we examined the effect of increasing suhu and excessed and depleted NO3 on growth rate, biomass and free fatty acid concentration in the Spirulina sp and Skeletonema sp. Two microalgae were culture on Conway and Milne media for 21 days using continuous culture technique. There were four temperature treatments, such as 28oC, 30oC, 32oC and 34oC and three nutrient treatments, which were control nutrient treatment, without NO3 and two times NO3 concentrations from control treatments with three replicates for each treatments. Results found that increasing temperature significantly affected on biomass and concentration free fatty acid, meanwhile nutrient treatments affected on growth rate, biomass and concentration of organic Carbon. In general, increasing temperature was more affected on Spirulina sp in terms of increasing growth rate, biomass and free fatty acid concentration. However, Skeletonema sp was more responsive to availability of NO3 in the media culture for increasing free fatty acid, and percentage of free fatty acid per dry weight.